Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1159/000059522
|View full text |Cite
|
Sign up to set email alerts
|

An Ecologic Study of Geographical Variation in Multiple Sclerosis Risk in Central Sardinia, Italy

Abstract: We carried out an ecological study in the most archaic area of Sardinia to obtain a reliable estimate of the prevalence of multiple sclerosis (MS) and to investigate the geographical variation in the prevalence across the 100 administrative communes. To estimate the area-specific prevalence rate, we adopted a Bayesian approach that makes it possible to filter out the random variation from the estimates and to obtain a map that reflects the true geographical variation in MS prevalence. 428 resident cases were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
(31 reference statements)
0
22
0
1
Order By: Relevance
“…Ï R = s/q (risk ratio to general population = risk for R-degree relative/risk in general population). 1 See reference [10]. Table 3 shows age-adjusted risks and risk ratios Ï R for different degrees of MS relatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ï R = s/q (risk ratio to general population = risk for R-degree relative/risk in general population). 1 See reference [10]. Table 3 shows age-adjusted risks and risk ratios Ï R for different degrees of MS relatives.…”
Section: Resultsmentioning
confidence: 99%
“…Malaria was also the reason for selecting some human leucocyte antigen alleles [8] and possibly some ancestral haplotypes which are particularly frequent in Sardinia but not in other parts of the world [9]. A high prevalence of MS (157/100,000 inhabitants, 103/ 100,000 inhabitants) and a high proportion of MS cases in the young age groups are reported in Sardinia, in particular in the Nuoro province and in the north-western part of the island [10,11]. An association between the ancestral haplotype A30B18DR3 and MS was also observed [12].…”
Section: Study Populationmentioning
confidence: 99%
“…New evidence has been reported that increased sun exposure during ages 6-15 y is associated with a decreased risk of multiple sclerosis (Van der Mei et al, 2003). Interestingly, the prevalence of MS among Sardinians presents evidence against the latitude gradient theory (Pugliatti et al, 2001) and could be explained by a high susceptibility of the population to MS (Montomoli et al, 2002).…”
Section: Ms and Vitamin Dmentioning
confidence: 99%
“…In recent years the Bayesian methodology has been strongly encouraged as an alternative to the frequentist approach when dealing with epidemio-logical data [13][14][15] and Bayesian mapping could be a better key to modeling the geographical distribution of a disease [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%